Comparison of conjunctival impression cytology between glaucoma patients treated with topical timolol maleate 0.5% and topicallatanoprost 0.005%. - Hitam, Wan Hazabbah Wan; Hoi, Tan Soon; Jaafar, Hasnan (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Introduction: All topical medications are known to cause conjunctival reactions, and topical antiglaucoma drugs are also no exception. Long term drug induced toxicity to the conjunctiva is postulated to cause filtering bleb scarring and filtration surgery failure. Chronic application of topical timolol maleate 0.5% and topical latanoprost 0.005% had been shown to alter the morphology of the conjunctival ocular surface. Objective: To compare conjunctival surface morphological changes with the use of the topical timolol maleate 0.5% and topicallatanoprost 0.005%. Methodology: Newly diagnosed glaucoma patients who met the selection criteria were randomly divided into two groups. One group treated with topical timolol maleate 0.5%, another group treated with topical latanoprost 0. 005%. Before the treatment was started, the first conjunctival impression cytology was taken. After three months of treatment, the second conjunctival impression cytology was obtained. The changes that occurred between thefrrst and second conjunctival impression cytology in the individual group were analyzed. Conjunctival surface changes that occurred with the use of topical timolol maleate 0.5% were also compared with the conjunctiva surface changes that occurred with the use of topicallatanoprost 0. 005%. Results: There were thirty-nine newly diagnosed glaucoma patients included in this study. Twenty patients were in the Timolol group and nineteen patients in the Latanoprost group. In both groups of patients, there was no change of the conjunctival epithelial cell morphology after three months of anti-glaucoma therapy. However, there was statistically significant reduction of the goblet cell and mucous granule density in both groups of patients after three months of the topical anti-glaucoma therapy (P- value <0.001). By using the independent T -test, there was no significant difference of the goblet cell and mucous granule density between the Timolol group and the Latanoprost group after three months of treatment. Conclusion: This concludes that both timolol maeate 0.5% and topicallatanoprost 0.005% cause great reduction of conjunctival goblet cells and mucous granules within three months of treatment. However, the conjunctival epithelial cell morphology remained normal after three month of treatment in both groups of patients. This study gives evidence that topical timolol maleate 0.5% and topicallatanoprost 0.005% cause morphological changes ofthe conjunctival surface after short term (three months) therapy. However, there was nodifference in the conjunctival morphological changes between the Timolol group and Latanoprost group.